2017
DOI: 10.1159/000468933
|View full text |Cite
|
Sign up to set email alerts
|

Decidual Bleeding as a Cause of Spontaneous Hemoperitoneum in Pregnancy and Risk of Preterm Birth

Abstract: Background: Spontaneous hemoperitoneum in pregnancy (SHiP) is a rare, life-threatening event, particularly relevant to women with endometriosis or deciduosis. Methods: To determine the type of lesions leading to SHiP, a literature search was conducted among all published SHiP cases. From a total of 1,339 publications, information on pathological findings at the bleeding site with histological data was found in 24 case reports (16 pregnant, 8 postpartum). Results: Among pregnant women (81% primigravida), 75% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The rare outcome SHiP is a potentially life-threatening condition during pregnancy. Lier et al found that bleeding originated from endometriotic implants, ruptured uteroovarian vessels, hemorrhagic nodules of decidualized tissue, or a combination of these [91] Spontaneous bowel perforations during pregnancy are mostly located in deep infiltrating bowel endometriosis in the sigmoid and rectum [92], and decidualization of these lesions represents a possible, yet unproven pathogenetic mechanism [79,93].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…The rare outcome SHiP is a potentially life-threatening condition during pregnancy. Lier et al found that bleeding originated from endometriotic implants, ruptured uteroovarian vessels, hemorrhagic nodules of decidualized tissue, or a combination of these [91] Spontaneous bowel perforations during pregnancy are mostly located in deep infiltrating bowel endometriosis in the sigmoid and rectum [92], and decidualization of these lesions represents a possible, yet unproven pathogenetic mechanism [79,93].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…In the process of pregnancy, estrogen and progesterone levels in the mother drastically increase until functional progesterone withdrawal at the end of pregnancy . Emerging evidence suggests that development of endometriosis‐associated SHiP is related to a drastic change in progesterone levels during pregnancy . This causes decidualization of endometriosis, leading to instability of parametrial arterioles and SHiP …”
Section: Discussionmentioning
confidence: 99%
“…A common complicating factor among those women who experienced a ruptured uterine vein was endometriosis and chronic pelvic inflammatory disease. The question remains, was the bleeding due to the in vitro fertilization or due to the inflammation and scarring of tissue in close proximity to uterine vessels? 5,6 …”
Section: Etiologymentioning
confidence: 99%
“…Some authors speculate that uterine vessels may be compromised due to the increased blood flow secondary to the increased blood volume during pregnancy. These compromised vessel walls may rupture during pregnancy or in the postpartum period 4,6 …”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation